Recent trends on glacier area retreat over the group of Nevados Caullaraju-Pastoruri (Cordillera Blanca, Peru) using Landsat imagery - Durán-Alarcón, Claudio (2015)
The Cordillera Blanca, located in the central zone of the Andes Mountains in Peru, has shown a retreat in its glaciers. This paper presents a trend analysis of the glacier area over the groups of Nevados Caullaraju-Pastoruri from 1975 to 2010 using Landsat-5 Thematic Mapper (TM) imagery. In the case of the Nevados Pastoruri/Tuco, the study period was extended back to 1957 by using an aerial photograph taken that year. The extent of clean glacier ice was estimated using Normalized Difference Snow Index (NDSI) thresholds. Moreover, the estimation of debris-covered glacier ice was retrieved by means of a decision tree classification method using NDSI, Normalized Difference Vegetation Index (NDVI) and Land Surface Temperature (LST). Area estimations derived from Landsat imagery were compared to the glacier ground-truth data in 1975 and 2010. Results show a statistically significant (p < 0.05) decreasing trend over the whole study area. Total glacier area decreased at a rate of 4.5 km2 per decade from 1975 to 2010, with a total loss of 22.5 km2 (58%). Lower decreasing rates were found for the period 1987–2010: 3.5 km2 per decade with a total loss of 7.7 km2 (32.5%). In the case of the Nevados Pastoruri/Tuco, decreasing rates of clean ice extent were constant for the periods 1957–2010, 1975–2010 and 1987–2010, with values close to 1.4 km2 per decade and a total loss between 1957 and 2010 estimated at about 5 km2 (54%). This work shows an evident area decrease in the Caullaraju-Pastoruri tropical glaciers, which needs to be included in a future hydrological scenario of local adaptability and water management.